Regionalna geografija in Ivan Gams - Perko, Drago (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
Regional geography of the second half of the 20th century is characterized by the regression of a theory and an exceptional development of methodology. The role of cartography and the knowledge on geographical names have increased during the last years. The human(istic) component of regional geography has been accentuated as well. On a national level, the importance of regional geography has grown significantly after the declaration of independence of Slovenia. I. Gams has mostly contributed to the development of Slovene regional geography with his regionalization of Slovenia and a secondary schooltextbook, with the leading of a long-lasting regional geographic scientific project, and as a mentor to young researchers.
Keywords: Gams, Ivan, 1923-; pokrajinska ekologija; regije; regional geography; regionalizacija; regionalna geografija